Garlic and Resveratrol Attenuate Diabetic Complications, Loss of β-Cells, Pancreatic and Hepatic Oxidative Stress in Streptozotocin-Induced Diabetic Rats - Kaur, Gagandeep; Padiya, Raju; Adela, Ramu; Putcha, Uday K.; Reddy, G. S.; Reddy, B. R.; Kumar, K. P.; Chakravarty, Sumana; Banerjee, Sanjay K. (Frontiers in Pharmacology, 2016)
Abstract:The study was aimed at finding the effect of garlic and resveratrol on loss of β-cells and diabetic complication in streptozotocin (STZ)-induced Type-I diabetic rats. Rats were injected with single dose STZ (50mg/kg, i.p.) for induction of type 1 diabetes (Dia) and compared with control group. Rats from third (Dia+Gar), fourth (Dia+Resv) and fifth (Dia+Met) groups were fed raw garlic homogenate (250 mg/kg/day), resveratrol (25 mg/kg/day) and metformin (500 mg/kg/day) orally, respectively for a period of 4 weeks. Diabetic group had decreased serum insulin and hydrogen sulfide levels along with increased blood glucose and glycated hemoglobin, triglyceride, uric acid and nitric oxide levels. Significant (p<0.05) increase in pancreatic and hepatic TBARS, conjugated dienes, nitric oxide, and AGE level and significant (p<0.05) decrease in SOD, catalase, H2S, GSH level were observed in diabetic group. Administration of garlic, resveratrol and metformin significantly (p<0.05) normalized most of the altered metabolic and oxidative stress parameters as well as histopathological changes. Administration of garlic, resveratrol and 9metformin in diabetic rat decreases pancreatic β-cell damage and hepatic injury. Our data concluded that administration of garlic showed more promising effect in terms of reducing oxidative stress and pathological changes when compared to resveratrol and metformin groups.